NEW YORK STRATEGIC PLAN (Tufts Archival Research Center, 2007)
New York State Strategic Plan for 1991. Lists favorable and unfavorable legislation and plans to work to pass and defeat it accordingly. States goals for relations with the business community, elected officials, the industry, the labor community, the press, and minorities. Expresses policital goals for the year.